Fine needle aspirate cell blocks are reliable for detection of hormone receptors and HER-2 by immunohistochemistry in breast carcinoma - Bueno Angela, S. P. [UNESP]; Viero, Rosa Marlene [UNESP]; Soares, C. T. (Wiley, 2013)
Aims: To evaluate the reliability of fine needle aspirate cell blocks in the assessment of oestrogen receptor (ER), progesterone receptor (PR) and HER-2/neu proteins by immunohistochemistry in comparison with surgical specimens. Materials and methods: This is a retrospective study of 62 cases of breast carcinoma diagnosed by fine needle aspiration cytology (FNAC) and confirmed using the surgical specimen. Immunohistochemical tests were performed to assess the presence of oestrogen receptor (ER), progesterone receptor (PR) and HER-2/neu proteins in cell blocks and the corresponding surgical specimens. The cell block method used alcohol prior to formalin fixation. Cases with 10% or more stained cells were considered positive for ER and PR. Positivity for HER-2/neu was assessed on a scale of 0-3+. The criterion for positivity was a score of 3+. Results: Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of the cell blocks in the investigation of ER, PR and HER-2/neu protein (3+) were (%): ER, 92.7, 85.7, 92.7, 85.7 and 90.3; PR, 92.7, 94.7, 97.4, 87.0 and 93.5; HER-2/neu, 70.0, 100.0, 100.0, 94.5 and 95.2. Discrepancies were seen in cell blocks in the 1+ and 2+ HER-2/neu staining scores: two of 12 cases scoring 2+ and one case of 26 scoring 1+ on cell blocks scored 3+ on surgical specimens. The correlation index between cell block and corresponding surgical specimen varied from 90% to 94%. Conclusion: Cell blocks provide a useful method of assessing ER, PR and HER-2/neu, mainly for inoperable and recurrent cases, but consideration should be given to carrying out FISH analysis on 1+ as well as 2+ HER-2/neu results. © 2012 Blackwell Publishing Ltd.
Keywords: Breast carcinoma; Cell block; Fine needle aspiration cytology; HER-2/neu; Hormone receptors; Immunocytochemistry; epidermal growth factor receptor 2; estrogen receptor; progesterone receptor; accuracy; breast carcinoma; cancer cell; cancer tissue; controlled study; fine needle aspirate cell block; fine needle aspiration biopsy; human; human cell; human tissue; immunohistochemistry; major clinical study; predictive value; priority journal; reliability; retrospective study; sensitivity and specificity; Biopsy, Fine-Needle; Breast Neoplasms; Female; Humans; Immunohistochemistry; Neoplasm Grading; Receptor, erbB-2; Receptors, Estrogen; Receptors, Progesterone; Reproducibility of Results; Retrospective Studies; Sensitivity and Specificity; Staining and Labeling; Tumor Markers, Biological